(untitled) (Journal of Medical & Health Sciences Review, 2025)
Introduction: In many low- and middle-income countries (LMICs), there are problems with how healthcare supplies are managed. These issues, like poor organization, divided systems, lack of responsibility, and frequent shortages, lead to worse health outcomes for people in those countries. In the last ten years, private-sector logistics collaborations and performance-based contracting (PBC) have been popular strategies for enhancing supply chain performance in environments with limited resources. Objectives: The structure, application, and effectiveness of PBC models in Pakistan’s donor-funded health supply chains from 2015 to 2025 are all critically examined in this review. Additionally, factors influencing private-sector logistics providers in LMICs are examined, and lessons learned are summarized to direct health supply chain reform in Pakistan by 2026. Methods: In order to assess PBC frameworks, operational, institutional, and market aspects as well as Public-Private Partnership (PPP) models impacting supply chains in LMICs, a comprehensive narrative review was carried out using a variety of regional and worldwide information. Results: PBC uses the idea of principle-agent theory, which means payments are tied to measurable goals. These goals include things like delivering supplies in time, keeping accurate records, and providing good quality reports. Countries like Tanzania, Zambia, and Afghanistan have shown that PBC can make healthcare more accessible and convenient. With the help of USAID GHSC-PSM, Pakistan has adopted PBC, which comprises PPP projects that concentrate on last-mile and cold chain distribution. Governmental opposition, inadequate digital systems, and restricted contract monitoring are some of the main obstacles. Resilience and efficiency are improved by strong control, defined responsibilities, uniform agreements, and market-shaping tactics like pooled procurement. Conclusion: To improve Pakistan’s health supply chain, we can focus on strengthening PBC, working more with private companies, using digital data, and employing market-shaping strategies. These changes are crucial by 2026 to build a more reliable, effective, and accountable system.